Quantum Cryptography Protocols Ensuring Secure Communication in the Era of Quantum Computing - J Kamalakumari; Kiran Ajmeera; Radha Gadige; Chandini Yedla; Tiwari Mohit; V Hemamalini (ITM Web of Conferences)
Quantum cryptography has emerged as a revolutionary technology for ensuring secure communication in the era of quantum computing. While existing research primarily focuses on theoretical frameworks and small-scale experimental setups, significant challenges remain in practical implementation, scalability, and security vulnerabilities. This study aims to bridge the gap between theory and real-world deployment by developing robust quantum cryptographic protocols that address key challenges such as noise management, side-channel attacks, and Trojan horse attacks. Additionally, we propose an optimized quantum key distribution (QKD) mechanism that ensures secure communication over long distances under realistic conditions. Our research integrates post-quantum cryptography with quantum cryptographic techniques to provide a hybrid security model that is resilient against both classical and quantum computing threats. By leveraging commercially available quantum hardware and advanced randomness extraction methods, this study contributes to the development of scalable, secure, and efficient quantum communication networks. The findings of this research will play a crucial role in advancing secure digital communication systems and fortifying data security in the post-quantum era.